Neuropteroides (Insecta: Neuroptera, Raphidioptera) en plantaciones de aguacate en el sur de España - Vela, J.M.=700 1 Boyero, J.R.; Wong, M.E.; Monserrat, V.J.
(Es, En)
Ilus., 48 ref.
Keywords: PERSEA AMERICANA; PLAGAS DE PLANTAS; NEUROPTERA; INSECTA; DEPREDADORES; AGENTES DE CONTROL BIOLOGICO; ACARINA; OLYGONICHUS PERSEAE; ESPAÑA